One for the books - McKinlay, Jenn (McKinlay, Jenn. Library lover's mysteries, 2020)
"Love is in the air in Briar Creek as library director Lindsey Norris and boat captain Mike (Sully) Sullivan are finally tying the knot. The entire town is excited for the happy day, and Lindsey and Sully's plan for a small wedding evaporates as more and more people insist upon attending the event of the year. When Lindsey and her crafternoon pals head out to Bell Island to see if it can accommodate the ever-expanding guest list, they are horrified to discover a body washed up on the rocky shore. Even worse, Lindsey recognizes the man as the justice of the peace who was supposed to officiate her wedding ceremony. When it becomes clear he was murdered, Lindsey can't help but wonder if it had to do with the wedding. Now she has to book-it to solve the mystery before it ends her happily ever after before it's even begun. . . "--